User-centric mobile app interface design for learning Malay sign language - Samsudin, Mat Redhuan; Daud, Noorlida; Sulaiman @Abd Rahim, Rushana (2024)
As technology continues to advance, there is a growing demand for user-friendly interfaces that cater to diverse needs. This study focuses on the interface design of a mobile application aimed at teaching sign language to a wide range of users. The interface design is crucial in ensuring an inclusive and accessible learning experience for individuals with hearing impairments. In this paper, we will explore the key considerations for designing an intuitive and effective sign language learning app interface, including visual elements, navigation, and interactive features. The goal is to provide a comprehensive guide for designers and developers to create an engaging and accommodating platform for learning sign language.